2014
DOI: 10.1002/cyto.b.21206
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and challenges in defining myeloid-derived suppressor cells

Abstract: Study of myeloid cells endowed with suppressive activity is an active field of research which has particular importance in cancer, in view of the negative regulatory capacity of these cells to the host's immune response. The expansion of these cells, called myeloid-derived suppressor cells (MDSCs), has been documented in many models of tumor-bearing mice and in patients with tumors of various origin, and their presence is associated with disease progression and reduced survival. For this reason, monitoring thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 125 publications
(268 reference statements)
1
68
0
4
Order By: Relevance
“…The CD11b C cells are usefully split into two subsets using the Ly6G marker. 23,24 As previously reported, 12 there was a predominance of the CD11b…”
Section: Marked Alterations Of the Myeloid Compartmentsupporting
confidence: 65%
“…The CD11b C cells are usefully split into two subsets using the Ly6G marker. 23,24 As previously reported, 12 there was a predominance of the CD11b…”
Section: Marked Alterations Of the Myeloid Compartmentsupporting
confidence: 65%
“…Numerous reports describe the presence of MDSC in murine tumors (reviewed in [22, 23]) and recent studies demonstrated that tumor associated MDSC have an important role in tumor progression [24, 25]. In humans, recent studies described the presence of MDSC in glioblastoma [26], urothelial carcinoma [27], pancreatic adenocarcinoma [7], and breast cancer [28].…”
Section: Regulation Of Mdsc Recruitment To Tumorsmentioning
confidence: 99%
“…Most studies on MDSC suppression have focused on cells in peripheral lymphoid organs (spleen, lymph nodes) and peripheral blood, mainly due to the technical challenges associated with MDSC isolation from tumors, which requires mechanical and enzymatic treatments that result in low recovery of MDSC and also impact cell function [23]. However, with technical advances in the isolation of myeloid cells from tumor tissues by using more gentle disaggregation of tissues with gentleMACS disaggregator ® (Miltenyi) or optimized dissociation protocols (one example described in [43]), it became clear that the mechanisms of MDSC action in the tumor site are different from the ones employed by these cells in peripheral lymphoid organs.…”
Section: Mechanisms Of Mdsc-mediated Immune Suppression Are Localizatmentioning
confidence: 99%
“…3 MDSCs are a heterogeneous population of immature myeloid cells that accumulate in blood, lymphoid organs, and tumor tissue under several pathologic conditions, including cancer. 3,4 MDSCs are generally characterized by being positive for CD33 and CD11b and low or negative for HLA-DR. 5 This population can be divided in 2 subgroups with different morphology. Monocytic (MO)-MDSCs are mononuclear and CD14 positive, whereas granulocytic or polymorphonuclear (PMN)-MDSCs are CD14 negative.…”
Section: Introductionmentioning
confidence: 99%
“…Monocytic (MO)-MDSCs are mononuclear and CD14 positive, whereas granulocytic or polymorphonuclear (PMN)-MDSCs are CD14 negative. 3,5 Both populations contribute to tumor immune escape by inducing immune suppression and tolerance through a variety of mechanisms, such as production of nitric oxide and reactive oxygen species, depletion of arginine and cysteine, and induction of regulatory T cells (Tregs). [6][7][8][9] However, their regulation and dynamics are poorly understood, especially in humans.…”
Section: Introductionmentioning
confidence: 99%